Olanzapine-induced DNA methylation in the hippocampus and cerebellum in genes mapped to human 22q11 and implicated in schizophrenia. (April 2015) - Melka, Melkaye G.; Rajakumar, Nagalingam; O'Reilly, Richard; Singh, Shiva M.
Abstract : Background: Although there is indirect evidence that the effects of antipsychotic drugs may involve modulation of dopamine transmission, their mechanism of action is poorly understood. We hypothesized that antipsychotic drugs mediate their effects by epigenetic modulation. Here, we tested the effect of an antipsychotic, olanzapine, on the DNA methylation status of genes following chronic treatment using rat-specific methylation arrays. Methods: Forty-eight hours after the last dose of olanzapine/vehicle, rats were habituated to an open-field activity-monitoring chamber for 30 min to verify whether stress-induced locomotor activity was reduced in olanzapine-treated rats. To test this hypothesis, we examined the effect of olanzapine, a commonly used atypical antipsychotic drug, on the DNA methylation status of 49 genes mapped to human 22q11 and implicated in schizophrenia. Genomic DNA isolated from the cerebellum, hippocampus, and liver of olanzapine-treated ( n =2) and control ( n =2) rats were analyzed using rat-specific methylation arrays. Results: Significantly reduced locomotor activity of olanzapine-treated rats confirmed the therapeutic efficacy of the drug administered. The effects of olanzapine have been shown through significantly increased ( P <0.01) DNA methylation of genes affecting several networks mainly (i) neurological disease, inflammatory disease, and inflammatory response and (ii) cancer, cell death and survival, tumor morphology. Also, proline degradation and L-DOPA degradation were affected by olanzapine-induced DNA methylation. Further, from a set of genes in the 22q11.2 microdeletions that has been implicated previously in psychosis, 29 genes showed increased methylation following olanzapine treatment. Conclusion: The results showed that considerable number of genes (34/49) mapped to human 22q11 and implicated in schizophrenia were affected by olanzapine-induced DNA methylation. The results suggest that DNA methylation may play a role in the therapeutic efficacy of olanzapine.